Dinamika Komunikasi Antarbudaya Awak Kabin pada Maskapai Multinasional: Studi Narrative Inquiry - Pratiwi Hidayat; Dylmoon Hidayat (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The global aviation industry involves frequent interactions among individuals from diverse cultural backgrounds, making intercultural communication an essential component of service delivery. However, research that specifically examines intercultural communication within airline service contexts, particularly studies using a narrative perspective focused on cabin crew experiences, remains limited. This study aims to analyze the dynamics of intercultural communication in multinational airline services by exploring the lived experiences of cabin crew as frontline service providers. The research adopts a qualitative approach with a narrative inquiry design, and data were collected through in-depth interviews with cabin crew members working for multinational airlines. The analysis is guided by Intercultural Adaptation Theory and Communication Accommodation Theory to understand how communication strategies are applied in multicultural service environments. The findings show that intercultural communication dynamics occur through three main processes: linguistic adaptation, negotiation of cultural norms and values, and the use of verbal and nonverbal accommodation strategies during service interactions. In addition, emotional sensitivity and awareness of cultural contexts emerge as important factors in maintaining effective communication and minimizing miscommunication. These findings indicate that intercultural communication functions not only as an interpersonal skill but also as a strategic competency that supports service quality in the global aviation industry.